Quorum Sensing and its Biotechnological Applications (Springer Singapore, 2018)
This book delves into the biotechnological applications of Quorum sensing (QS)- a peculiar gene-regulatory process of some microorganisms. Quorum Sensing allows a large bacterial population to work together in a coordinated manner to carry out metabolic activities, which individual bacterium cannot. The different chapters describe how, associating bioremediation process with energy generation is an economical proposal, for reducing pollution and managing biowastes. The book discusses how QS can be exploited for biotechnological applications in generating bioproducts, bioenergy, bioremediation, biosensors, health and agricultural activities. It further highlights how QS is becoming an integral part of synthetic biology for genetic circuits for producing: (i) novel products, (ii) biosensors, (iii) bioactive molecules, etc. The book is divided into different sections for a clear understanding of the applicability of QS in, the Environment, Energy, Agriculture and Health sectors.